2009
DOI: 10.1177/147323000903700610
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Lymphocyte Subsets in the Peripheral Blood of Patients with Active Pulmonary Tuberculosis

Abstract: The aim of this study was to determine the percentage of lymphocyte subsets in peripheral blood in patients with active tuberculosis. A total of 21 patients with active tuberculosis and 15 healthy volunteers were included in the study. T-lymphocyte subsets, B-lymphocytes (CD19(+) cells), natural killer (NK) cells and cells positive for costimulatory molecules CD28 and CD152 were evaluated using flow cytometry. Patients with tuberculosis had a significantly decreased percentage of CD3(+) and CD3(+)CD4(+) cells,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
33
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 24 publications
7
33
0
Order By: Relevance
“…For example, some studies suggest that the percentages of B cells are lower in TB patients than in HS [28,50]. Other studies indicates that the percentage of B cells is either higher or similar between PTB patients and HS [51,52]. In our study PTB and PLTB patients had a higher proportion of B cells than HS.…”
Section: Discussionsupporting
confidence: 53%
“…For example, some studies suggest that the percentages of B cells are lower in TB patients than in HS [28,50]. Other studies indicates that the percentage of B cells is either higher or similar between PTB patients and HS [51,52]. In our study PTB and PLTB patients had a higher proportion of B cells than HS.…”
Section: Discussionsupporting
confidence: 53%
“…In some reports, a reduction in the frequency of peripheral-blood NK cells has been observed in TB patients when compared to healthy donors [87,88]. However, other studies have not found a difference [90,91] or have reported an increase in the peripheral-blood NK cell count in TB patients compared to healthy individuals [89]. The discrepancy encountered in the number of NK cells in the peripheral blood of TB patients compared to healthy donors in different studies could be due to: (1) differences in the stage and gravity of the TB infection in the patients included in the studies [92], (2) the MTB strain involved or (3) the presence/absence and duration of anti-TB antibiotic therapy [87,91].…”
Section: Evidence Of a Role Of Nk Cells In Human Tb: Clinical Studiesmentioning
confidence: 97%
“…In humans, several clinical studies have explored the potential association between NK cell counts in the peripheral blood (CD3 - CD56 + ) and TB [87,88,89,90,91]. In some reports, a reduction in the frequency of peripheral-blood NK cells has been observed in TB patients when compared to healthy donors [87,88].…”
Section: Evidence Of a Role Of Nk Cells In Human Tb: Clinical Studiesmentioning
confidence: 99%
See 2 more Smart Citations